2009
DOI: 10.1002/jnr.22243
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect between proteasome and autophagosome in the clearance of polyubiquitinated TDP‐43

Abstract: Cytoplasmic aggregates of ubiquitinated TAR DNA-binding protein 43 (TDP-43) are a pathological hallmark of amyotrophic lateral sclerosis (ALS). However, the mechanism of TDP-43 polyubiquitination remains elusive. We investigated the effect of nuclear exclusion of TDP-43 on aggregate formation and fragmentation, using TDP-43 expression constructs for WT or mutant TDP-43 with a modified nuclear localizing signal (LQ-NLS). Overexpression of the LQ-NLS mutant alone induced no detectable cytoplasmic aggregates duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 30 publications
8
90
4
1
Order By: Relevance
“…S2A). Similar to the previous findings (Urushitani et al, 2010), the half-lives of the full-length Myc-hTDP-43 and the truncated MychTDP-35 and Myc-hTDP-25 were ,16-18 h, ,10 h and ,7.6 h, respectively ( Fig. 3B; supplementary material Fig.…”
Section: Cleavage Of the Full-length Tdp-43 Into Tdp-35 And Tdp-25 Frsupporting
confidence: 89%
See 1 more Smart Citation
“…S2A). Similar to the previous findings (Urushitani et al, 2010), the half-lives of the full-length Myc-hTDP-43 and the truncated MychTDP-35 and Myc-hTDP-25 were ,16-18 h, ,10 h and ,7.6 h, respectively ( Fig. 3B; supplementary material Fig.…”
Section: Cleavage Of the Full-length Tdp-43 Into Tdp-35 And Tdp-25 Frsupporting
confidence: 89%
“…To date, several studies have reported findings regarding the degradation of the TDP-43 protein. In particular, it has been found that overexpressed full-length TDP-43 protein and its truncated 25 kDa and 35 kDa fragments are degraded through both the ubiquitin proteasome system (UPS) (Kim et al, 2009;Urushitani et al, 2010;Wang et al, 2010) and macroautophagy pathways (Caccamo et al, 2009;Filimonenko et al, 2007;Ju et al, 2009;Wang et al, 2012). Most short-lived proteins are degraded by UPS through the 26S proteasome (DeMartino and Slaughter, 1999), whereas the autophagy-lysosomal pathway primarily catabolizes unnecessary organelles, long-lived proteins and misfolded and/or aggregated proteins (Ravikumar et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…First, we introduce a novel method by which we can distinguish how a given pathway or modifier affects protein accumulation. Different degradation pathways have been implicated in affecting the accumulation of aggregation-prone proteins, from proteasome-mediated degradation (Mishra et al, 2008;Iwata et al, 2009;Zhang et al, 2010;Urushitani et al, 2010;Ortega and Lucas, 2014;Schipper-Krom et al, 2014) to the lysosome-mediated pathway or macroautophagy as being the predominant pathway for aggregate clearance (Ravikumar et al, 2002;Iwata et al, 2005b;Yamamoto et al, 2006;Pankiv et al, 2007;Lamark et al, 2009;Fan et al, 2010;Lamark and Johansen, 2012;Odagiri et al, 2012;Castillo et al, 2014;Bae et al, 2014). Our ability to interrogate how each pathway might contribute to aggregate turnover has been limited by our inability to temporally characterize aggregate formation and clearance in cells.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, inhibition of the autophagy compromises the ubiquitin-proteasome pathway (36,37). Evidence has been presented before that clearance of TDP-43 and its caspase-generated 35-and 25-kDa fragments is processed through both the autophagy (48 -50) as well as the proteasome pathway (48,49). For instance, use of the autophagy inhibitors such as 3-MA (49) and autophagy activators such as rapamycin (50) increases and reduces, respectively, the accumulation of TDP-43.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has been presented before that clearance of TDP-43 and its caspase-generated 35-and 25-kDa fragments is processed through both the autophagy (48 -50) as well as the proteasome pathway (48,49). For instance, use of the autophagy inhibitors such as 3-MA (49) and autophagy activators such as rapamycin (50) increases and reduces, respectively, the accumulation of TDP-43. Also, TDP-43 interacts with ubiquilin, a polyubiquitin-binding protein that is involved in both autophagy and UPS (51,52).…”
Section: Discussionmentioning
confidence: 99%